(untitled) (International Journal of Engineering and Computer Science, 2017)
Active database systems support mechanisms that enable them to respond automatically to events that are taking place either inside or outside the database system itself. Considerable effort has been directed towards improving understanding of such systems in recent years, and many different proposals have been made and applications suggested. This high level of activity has not yielded a single agreed-upon standard approach to the integration of active functionality with conventional database systems, but has led to improved understanding of active behaviour description languages, execution models, and architectures. This paper presents the fundamental characteristics of active database systems[11], describes a collection of representative systems within a common framework, considers the consequences for implementations of certain design decisions, and discusses tools for developing active applications. Active database management systems are invoked by synchronous events generated by user or application programs as well as external asynchronous data change events such as a change in sensor value or time. In this paper gives the introduction of active DBMS[12] and discussed how it is different from passive DBMS.